The functioning of a legal institution of grace in canonical legal system - GIERŻON, GINTER (Prawo Kanoniczne, 2014)
The author of the presented article reflected on the issue of a legal institution of grace in canonical legal order. The analyses carried out by the author showed that the approach of the ecclesial legislator evolved. He moved from the reistic understanding of this institution putting the emphasis on its theological-personal dimension. The author proved that according to the conventional assumptions, the acts of grace favour an individual who finds himself in circumstances unexpected in the law. For this reason, ecclesiastical power while taking any action in a particular case should take into account the specificity of the situation the faithful is in but should also consider if the decision made would lead to his salvation (can. 1752 CIC).